The beauty of Korea - Suh, Jai-sik (Elizabeth, NJ : Hollym Internatuinal Corp., 1997)
The Beauty of Korea gives some insight and understanding into the nature of Korea and Koreans.
Keywords: Koreans -- Pictorial works; Korea -- Social life and customs; Korea -- History; Korea -- Description and travel; Korea -- Pictorial works